Hubungan Faktor Pelayanan Kesehatan Kerja dengan Tingkat Kepuasan Karyawan Berdasarkan Persepsi Karyawan - Wiwik Dian Cahyani (Universitas Pekalongan, 2010)
he drinking water factory in Ungaran who have the health services was preserved for employees during the work. The health services consist of the health services activity, health officer competency, equipment and health facility and health insurance. The problem of this research is about health service factors that influence to employees satisfaction. The aim of research are to know about relation between health services, health officer competency, equipment and facility, health insurance with the employees satisfaction on the company. The design of research with used cross section approach. The technique which had used on taking the sample is random sampling or random with used simple formulae to ensure proportion and degrees of accuration on the level of statistic which significance so that got sample amount 153 persons. The technique to taking data is used questionnaire and obsevation paper. The analysis data is used chi square test with looking the coefficient of contingency and the value of probility to know relation between health service and employees satisfaction level. The results of research shown that the service quality is good and 70.4% of employees satisfied. The capability of health officer is poor that 84,7% of employees are not satisfied, facility and equipment quality is good that 57,9 % satisfied and health insurance quality is good, 68% satisfied. Suggestion to improve the level of employees satisfaction to the health service in the company are the company could increase the current health service for employees more satisfied and making simple process to arrange the health insurance procedures.Keywords : health occupational and employees satisfaction level